Association between serum albumin and glycated hemoglobin in Asian Indian subjects - Tiwari, Shalbha (Indian J Endocrinol Metab, 2015)
BACKGROUND: Protein glycation plays a significant role in diabetic complications. Glycated hemoglobin (HbA1c) is a known predictor of diabetes and its complications. Albumin, found to be profoundly glycated in diabetes, and its level could regulate plasma protein as well as hemoglobin glycation. AIM: We aimed to evaluate the association between variations in albumin level with HbA1c in the Asian Indian population. MATERIALS AND METHODS: We screened data of 929 subjects who have had a simultaneous measurement of fasting plasma glucose (FPG), HbA1c and albumin levels via the same blood collection. Data were analyzed by SPSS for 610 subjects who met the study criteria. RESULTS: There was a significant negative correlation between HbA1c and albumin concentration (r = −0.284; P < 0.001). Univariate analysis showed the statistically significant decrease of average HbA1c but not for fasting plasma glucose (FPG) across increasing tertiles of albumin. Stepwise multiple regression model showed a significant correlation between HbA1c and serum albumin (P < 0.05), FPG (P < 0.001), hemoglobin (Hb) (P < 0.001) and serum globulin (P < 0.05). FPG was the strongest predictor (63.4%) of variation of HbA1c. The albumin concentration (r = −0.114) accounted for 0.3% (P < 0.05) of the total variance in HbA1c independent of age, body mass index, FPG, Hb, creatinine, total protein and globulin. It was also observed that HbA1c decreases with increasing albumin concentration in those having FPG between 100 to <126 mg/dl. CONCLUSION: Serum albumin negatively correlates with HbA1c in Asian Indians independent of other variables. This study suggests that predicting diabetes and its complication based on the HbA1c needs to be further investigated in Indian subjects.